In vitro immune response of chinook salmon (Oncorhynchus tshawytscha) peripheral blood mononuclear cells stimulated by bacterial lipopolysaccharide. Issue 94 (November 2019) - Lulijwa, Ronald; Alfaro, Andrea C.; Merien, Fabrice; Burdass, Mark; Venter, Leonie; Young, Tim
Abstract: We investigated cellular functional and targeted immune cytokine responses of farmed Chinook salmon ( Oncorhynchus tshawytscha ) peripheral blood mononuclear cells (PBMCs) in vitro to LPS from Escherichia coli ( E. coli ) serotypes O111: B4 and O55: B5, and a phorbol ester phorbol 12-myristate 13-acetate (PMA). Bacterial LPS and PMA significantly (p < 0.05) induced reactive oxygen species (ROS) production in O. tshawytscha PBMCs, and enhanced by interferon (IFN)-inducible cytokine production. Cellular phagocytosis was significantly enhanced with PMA and E. coli serotype O111: B4 LPS after 1 and 2 h respectively. At the molecular level, LPS and PMA significantly (p < 0.05) upregulated pro-inflammatory cytokine gene transcripts for IFNγ, TNF-α, and anti-inflammatory IL-10, 24 h post-stimulation. This response is postulated to be mediated via the MyD88 and TRIF pathways in TLR4, or synergistic TLR1 and TLR2 receptors. This is the first report of LPS induced immune related in vitro responses in farmed O. tshawytscha PBMCs. Highlights: Bacterial LPS and PMA significantly stimulated fish PBMC ROS production. LPS and PMA significantly enhanced chinook salmon PBMC phagocytosis. LPS and PMA upregulated PBMC pro-inflammatory IFNγ and TNF-α cytokines. LPS and PMA stimulated PBMC ant-inflammatory IL-10 cytokine production.